Clinically Significant Differences in Ki-67 Proliferation Index Between Primary and Metastases in Resected Pancreatic Neuroendocrine Tumors. Issue 10 (November 2017) - Richards-Taylor, Sebastian; Tilley, Charles; Jaynes, Eleanor; Hu, Haixiao; Armstrong, Thomas; Pearce, Neil W.; Plant, Rachel; Cave, Judith
Abstract : Objective: Pancreatic neuroendocrine tumors (NETs) (pNETs) have a varied prognosis according to their grade. The European Neuroendocrine Tumor Society grading system uses assessment of the proliferation index via Ki-67 immunohistochemistry to aid prognosis. There is evidence that the proliferation index can vary significantly within a single tumor, but it is not fully understood to what extent heterogeneity occurs between the primary and metastatic sites and how this may affect the grade. The aim of this study is to determine whether the grade assigned to a pNET varies depending on which site is selected for Ki-67 immunolabeling. Methods: Patients were selected from our institution's NET database. Patients were included if they had a confirmed pNETs, had multiple resection specimens, and had consented to research being performed on their specimens. Ki-67 immunohistochemistry was performed on all resected specimens meeting the inclusion criteria. Results: Pancreatic neuroendocrine tumors specimens resected from 16 patients were analyzed. There was no trend to higher Ki-67 in metastatic than primary disease. Ki-67 was on average 3% higher in liver metastases than lymph node metastases ( P < 0.001). Conclusions: The grade of pNETs varies according to the tumor selected for Ki-67 immunolabeling. Useful information can be gained by performing Ki-67 PI on liver metastases.